Analytical Study of Cooperative Organizations Based on Domestic Area of Asian Countries: A Classical Approach of Village - Sahani, Suresh Kumar; Karna, Santosh Kumar (Darul Yasin Al Sys, 2024)
In this research paper, we have studied the role of cooperative societies in rural area of asian countries especially in Madhesh Province of Nepal. Also we study the liqidity position of these societies in economic development of rural area of our country.